PENGARUH PENERAPAN STRATEGI BELAJAR AKTIF TIPE INDEX CARD MATCH TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X SMAN 15 PADANG - Sanjaya, Hendrik; Aima, Zulfitri; Haryono, Yulia (Pendidikan Matematika, 2014)
ABSTRACTThis research is motivated by studentsâ comprehensian of mathematical concept that stiil low and studentsâ participate in learning as less. The purpose of this research is to determine whether studentsâ comprehensian of mathematical concept by implementing active learning type index card match is better than studentsâ comprehension of mathematical concept by implementing conventional learning in class X SMAN 15 Padang school year 2013/2014. This was an experiment research. Sampling was done randomly, which was selected X3 as experiment class and X5 as control class. The instrument used is final test that contains an indicator of comprehension concept with reliability test is . The data was analyzed by using to test with MINITAB software. Based on the result of data analysis, it was revealed that the sample has normally distributed and homogeneus with Î± = 0,05. Hypothesis test result obtained that P-value = 0,031 is smaller than Î± = 0,05, so hypothesis was received. It can be conclude that studentsâ comprehension of mathematical concept by implementing active learning type index card match is better than student comprehension of mathematical concept by implementing conventional learning in class X SMAN 15 Padang